A taxonomic review of the trapdoor spider genus Promyrmekiaphila Schenkel (Araneae, Mygalomorphae, Cyrtaucheniidae, Euctenizinae) - Stockman, Amy; Bond, Jason E. (Zootaxa, 2008)
The mygalomorph spider genus Promyrmekiaphila comprises two species known from northern and central California. The type species, P. clathrata (Simon), is considered a senior synonym of P. gertschi Schenkel and P. zebra (Chamberlin & Ivie); male and female exemplar specimens are described. A new species, Promyrmekiaphila winnemem, from Shasta and Tehama Counties in northern California, is described.